2018
DOI: 10.1002/jcp.27572
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA APTR contributes to osteosarcoma progression through repression of miR‐132‐3p and upregulation of yes‐associated protein 1

Abstract: A growing amount of evidence has shown that long noncoding RNAs (lncRNAs) play crucial roles in osteosarcoma (OS). However, little knowledge is available about the functional roles and molecular mechanisms of lncRNA Alu‐mediated p21 transcriptional regulator (APTR) in OS. Herein, APTR expression was demonstrated to be significantly upregulated in OS tumor tissues and four OS cell lines (including MG63, 143B, Saos‐2, and HOS) compared with the adjacent tissues and human osteoblast cell line hFOB1.19, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…As we know, Hippo pathway, especially the dysfunction of YAP1 plays tumor-promoting actions in several human cancers [20][21][22][23][24]. Our previous findings demonstrated that YAP1 expression was upregulated in OSC cells [8], which were confirmed in this study.…”
Section: Discussionsupporting
confidence: 87%
“…As we know, Hippo pathway, especially the dysfunction of YAP1 plays tumor-promoting actions in several human cancers [20][21][22][23][24]. Our previous findings demonstrated that YAP1 expression was upregulated in OSC cells [8], which were confirmed in this study.…”
Section: Discussionsupporting
confidence: 87%
“…Over the past few years, previous studies have reported that non-coding RNAs, including miRNAs and long non-coding RNAs, serve important roles in cancer (23)(24)(25). For example, miR-543 was observed to promote ESCC cell migration, invasion and EMT via targeting phospholipase A2 Group IVA (26).…”
Section: Discussionmentioning
confidence: 99%
“…In osteosarcoma (OS), ANRIL has been reported to be closely associated with the malignant behavior of OS cells (9). In addition, APTR has been reported to inhibit miR-132-3p and upregulate YAP1 to accelerate OS progression (34). In hepatocellular carcinoma, DLGAP1-AS1 has been confirmed to facilitate cell proliferation via the miR-486-5p/H3F3B axis (35).…”
Section: Discussionmentioning
confidence: 99%